(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
The Italian-Syrian joint Mission of the Università degli Studi of Milan at Palmyra (Pal.M.A.I.S. = Palmira. Missione Archeologica Italo-Siriana) is focus on the exploration of the south-west quarter of the ancient city. Since 2008 the stratigraphic excavation of the "Peristyle Building" has begun. Many fragments of stucco which are part of a frieze decorated by an Anthemion have been found in one room of the building - the room A -. These fragments belong to the decoration of a luxury complex which was damaged (or destroyed?) before the 6th century AD, and they are very important elements in order to define the chronological horizon of the first phase of development of the area.